PENINGKATAN KETERAMPILAN PASSING BAWAH DALAM PEMBELAJARAN BOLA VOLI MENGGUNAKAN BOLA PLASTIK - Eni Nur Atmianti; Heni Yuli Handayani; Khoirul Anwar; Septyaningrum Putri Purwoto (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2022)
The problem in this study is whether a plastic ball can improve volleyball bottom passing learning outcomes in X AKL 1 SMKN 1 Kamal students. The purpose of this research was to improve the technique of learning volleyball underpassing for class X AKL 1 students through sponge plastic ball media. The method used in this research was classroom action research. The total number of students in class X AKL 1 in 28 female students. Down passing learning using plastic ball sponges on X AKL 1 SMKN 1 Kamal students for 2 cycles could produce student learning achievement, this could be proven from the results of learning observations that have been carried out, the data obtained are complete learning outcomes as follows: pre-cycle 25% cycle 1 is 65% and cycle 2 is 100%. This study concluded that there was an improvement in lower passing skills in learning volleyball using a plastic ball.